What it means to be Palestinian stories of Palestinian peoplehood - Matar, Dina (I.B. Tauris, 2011)
A collection of personal stories, remembered feelings and reconstructed experiences by different Palestinians whose lives were changed and shaped by history. It tells their stories chronologically through particular phases of the Palestinian national struggle, providing an autobiography of Palestine as a landscape and as a people